Immunotherapeutic effects of recombinant adenovirus encoding interleukin 12 in experimental pulmonary tuberculosis. (24th January 2019) - Mata‐Espinosa, Dulce Adriana; Francisco‐Cruz, Alejandro; Marquina‐Castillo, Brenda; Barrios‐Payan, Jorge; Ramos‐Espinosa, Octavio; Bini, Estela Isabel; Xing, Zhou; Hernández-Pando, Rogelio
Abstract: High dose of Mycobacterium tuberculosis (Mtb) strain H37Rv administered by intratracheal injection in BALB/c mice induce progressive tuberculosis (TB). In this model, during the first month there is a temporal control of bacillary growth, in coexistence with macrophage activation, granuloma formation and Th‐1 response. Then, bacterial proliferation recommences, accompanied by progressive pneumonia and decreasing expression of protective cytokines (IFN‐γ and TNF‐α). In this model, we studied the IL‐12 gene expression kinetics and cellular source. There is a rapid and progressive IL‐12 expression peaking at day 14, when granulomas start their formation and numerous macrophages show strong IL‐12 immunostaining, while during progressive TB there is a significant decrease of IL‐12 expression and occasional macrophages showed IL‐12 immunolabeling. In the second part of this study, we determined the immunotherapeutic effect of recombinant adenoviruses that codify IL‐12 (AdIL‐12). Intratracheal administration of only one dose of AdIL‐12 one day before Mtb infection produced significant decrease of bacterial loads, lesser pneumonia and higher expression of TNF‐α, IFN‐γ and iNOS. When only one dose of AdIL‐12 was given in healthy mice cohoused with infected mice with highly virulent and transmissible Mtb, total prevention of infection was conferred. Moreover, when AdIL‐12 was administered by intranasal route in animals suffering late active TB after 2 months of infection, a very low pulmonary bacilli burdens was detected. These experimental data confirm that IL‐12 is a significant cytokine in the immune protection against Mtb, and gene therapy based in adenoviruses coding this cytokine increased protective immunity and prevent Mtb transmission.